"Looks Can be Deceptive" – Radicular Cyst Mimicking a Developmental Origin Cyst. Issue 7 (October 2021) - Khan, Imran; Ansari, Mohammad Irfan; Mansoori, Shahnaz; Saalim, Mohd.
Abstract : Abstract: Cysts of the jaws are not rare, among them the radicular cyst being the most common. It is an inflammatory type of odontogenic cyst forming as a consequence of a long-standing sequel of pulpal necrosis. In contrast to its usual location of occurrence (ie, the maxilla), herewith we report a case of successful management of a 45 year old female patient with a large radiolucent lesion in the left mandibular posterior region with a mandibular ramus extension. The pathology which was strongly presenting as a developmental variety of odontogenic cyst radiographically, was diagnosed as a radicular cyst after histopathological confirmation. To the authors best of knowledge radicular cyst extending into the mandibular ramus is extremely rare and has never been reported previously.